Analysis of the Epigenome in Multiplex Pre-eclampsia Families Identifies SORD, DGKI, and ICA1 as Novel Candidate Risk Genes - Ariff, Amir; Melton, Phillip E.; Brennecke, Shaun P.; Moses, Eric K. (Frontiers in Genetics, 2019)
Pre-eclampsia is a serious heritable disorder that affects 5-8% of pregnancies worldwide. While classical genetic studies have identified several susceptibility genes they do not fully explain the heritability of pre-eclampsia. An additional contribution to risk can be quantified by examining the epigenome, in particular the methylome, which is a representation of interactions between environmental and genetic influences on the phenotype. Current array-based epigenetic studies only examine 2-5% of the methylome. Here, we used whole-genome bisulfite sequencing (WGBS) to determine the entire methylome of 13 individuals from two multiplex pre-eclampsia families, comprising one woman with eclampsia, six women with pre-eclampsia, four women with uncomplicated normotensive pregnancies and two male relatives. The analysis of WGBS profiles using two bioinformatics platforms, BSmooth and Bismark, revealed 18,909 differentially methylated CpGs and 4157 differentially methylated regions (DMRs) concordant in females. The methylation patterns support the involvement of previously reported candidate genes, including COL4A1, SLC2A4, PER3, FLT1, GPI, LCT, DDAH1, TGFB3, DLX5, and LRP1B. Statistical analysis of DMRs revealed three novel genes significantly correlated with pre-eclampsia: sorbitol dehydrogenase (SORD, p=9.98 x 10-6), diacylglycerol kinase iota (DGKI, p=2.52 x 10-5), and islet cell autoantigen 1 (ICA1, 7.54 x 10-3), demonstrating the potential of WGBS in families for elucidating the role of epigenome in pre-eclampsia and other complex diseases.